The Wiskott-Aldrich syndrome protein (WASP) is essential for myoblast fusion in Drosophila. - Schafer, G.; Weber, S.; Holz, A.; Bogdan, S.; Schumacher, S.; Muller, A.; Renkawitz-Pohl, R.; Onel, S.F. (Developmental Biology, 2007)
In higher organisms, mononucleated myoblasts fuse to form multinucleated myotubes. During this process, myoblasts undergo specific changes in cell morphology and cytoarchitecture. Previously, we have shown that the actin regulator Kette (Hem-2/Nap-1) is essential for myoblast fusion. In this study, we describe the role of the evolutionary conserved Wiskott-Aldrich syndrome protein that serves as a regulator for the Arp2/3 complex for myoblast fusion. By screening an EMS mutagenesis collection, we discovered a new wasp allele that does not complete fusion during myogenesis. Interestingly, this new wasp3D3-035 allele is characterized by a disruption of fusion after precursor formation. The molecular lesion in this wasp allele leads to a stop codon preventing translation of the CA domain. Usually, the WASP protein exerts its function through the Arp2/3-interacting CA domain. Accordingly, a waspDeltaCA that is expressed in a wild-type background acts as dominant-negative during the fusion process. Furthermore, we show that the myoblast fusion phenotype of kette mutant embryos can be suppressed by reducing the gene dose of wasp3D3-035. Thus, Kette antagonizes WASP function during myoblast fusion.